Therapeutic Potential of Autologous Stem Cell Transplantation for Cerebral Palsy. (4th October 2012) - Purandare, Chaitanya; Shitole, D. G.; Belle, Vaijayantee; Kedari, Aarti; Bora, Neeta; Joshi, Meghnad
Abstract : Background . Cerebral palsy (CP) is a severe disabling disease with worldwide incidence being 2 to 3 per 1000 live births. CP was considered as a noncurable, nonreparative disorder, but stem cell therapy offers a potential treatment for CP. Objective . The present study evaluates the safety and efficacy of autologous bone-marrow-derived mononuclear cell (BMMNCs) transplantation in CP patient. Material and Methods . In the present study, five infusions of autologous stem cells were injected intrathecally. Changes in neurological deficits and improvements in function were assessed using Gross Motor Function Classification System (GMFCS-E&R) scale. Results . Significant motor, sensory, cognitive, and speech improvements were observed. Bowel and bladder control has been achieved. On the GMFCS-E&R level, the patient was promoted from grade III to I. Conclusion . In this study, we report that intrathecal infusion of autologous BMMNCs seems to be feasible, effective, and safe with encouraging functional outcome improvements in CP patient.